The Effects of a Linguistic Tsunami on the Languages of Aceh - Zulfadli A. Aziz; Robert Amery (Studies in English Language and Education, 2016)
The languages throughout the world are in crisis and it is estimated that 50% to 90% will have disappeared by the end of this century (Grenoble, 2012). Colonisation, nationalism, urbanisation and globalisation have resulted in a linguistic tsunami being unleashed, with a few major world languages swamping others. The rate of language loss today is unprecedented as this small number of dominant languages expands rapidly. Small minority languages are mainly in danger, but even large regional languages, such as Acehnese with millions of speakers, are unsafe. Similar to the case of a tsunami triggered by an earthquake, it is generally too late before speakers are aware of what is happening. In most cases language shift will have already progressed and irreversible before people realize it. This paper examines the early warning signs of impending language shift and what can be done for minority languages to have the best chance of survival. We draw on the local situation in Aceh, as well as other parts of the Austronesian speaking world and Australia, where the record of language loss is the worst in the world. Language shift in Australia is well-progressed; in Indonesia it is more recent. Lessons learned from places such as Australia and Taiwan have relevance for Indonesia today.